1999
DOI: 10.4319/lo.1999.44.3_part_2.0878
|View full text |Cite
|
Sign up to set email alerts
|

Using chlorophyll a fluorescence to detect the onset of anthracene photoinduced toxicity in Lemna gibba, and the mitigating effects of a commercial humic acid

Abstract: The influence of a commercial humic acid (Aldrich; AHA) on the development of anthracene photoinduced toxicity to the duckweed Lemna gibba was examined using both room-and low-temperature (77ЊK) chlorophyll fluorescence assays. Plants were exposed to 2 mg liter Ϫ1 anthracene both with and without 6.2 mg liter Ϫ1 of AHA and grown under either visible light or simulated solar radiation that mimics the natural abundance of UV radiation. Exposure periods ranged from 1 to 48 h to examine temporal changes in chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…The results presented were in line with other similar studies, which demonstrated the inhibition of photosynthetic system by DDTs in microalgae (Powers Samson and Popovic 1988). The use of fluorescence parameters to detect PAHs toxicities has also been reported in vascular plant (Gensemer et al 1999).…”
Section: Resultssupporting
confidence: 92%
“…The results presented were in line with other similar studies, which demonstrated the inhibition of photosynthetic system by DDTs in microalgae (Powers Samson and Popovic 1988). The use of fluorescence parameters to detect PAHs toxicities has also been reported in vascular plant (Gensemer et al 1999).…”
Section: Resultssupporting
confidence: 92%
“…Laboratory experiments with aquatic organisms ranging from duckweed to Daphnia and fish have demonstrated that humic substances can reduce the toxicity of polycyclic aromatic hydrocarbons such as anthracene (Oris et al 1990;Gensemer et al 1999). DOC reduces the bioavailability of PCBs during acidification (Knulst 1992), and also reduces the toxicity of aluminum and copper to fish (Driscoll et al 1980;Welsh et al 1993).…”
Section: Increases Attenuation Of Solar Radiationmentioning
confidence: 99%
“…Oris et al 1990;Gensemer et al 1999 • reduces the bioavailability of PCBs Knulst 1992 • alters availability of P, Fe, and C of different molecular weights and thus C cycle, energy supply, productivity, and eutrophication Stewart and Wetzel 1982;Francko 1986;Hessen 1992;Hobbie 1992;De Haan 1993;Herndl et al 1993;Lindell and Rai 1994 4. Interferes with drinking water purification • use of strong oxidants such as chlorine and ozone produce toxic disinfection by-products (DBPs) such as trihalomethanes (THMs) Edzwald et al 1985;Krasner et al 1989;Reckhow and Singer 1990 • ozonation produces aldehydes such as formaldehyde Nawrocki and Kalkowska 1995;Krasner et al 1989 • reacts with oxidizing disinfectants to reduce their effectiveness Harrington et al 1996 in rivers in late winter and early spring (Hornberger et al 1994).…”
Section: Increases Attenuation Of Solar Radiationmentioning
confidence: 99%
“…In that work, variable fluorescence was assessed using DCMU addition for maximum fluorescence measurements. Comparing fluorescence to chlorophyll concentration, Gensemer et al (1999) found fluorescence variables to respond earlier to anthracene exposure. To the best of our knowledge, none of the studies published measured fluorescence by means of a fast repetition rate fluorometer (FRRF).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, fluorescence is proving to be more sensitive than classical endpoints due to its sublethal but ecologically relevant character (i.e. Gensemer et al 1999;Pérez et al 2006;Pérez et al 2009;Pérez et al, in preparation).…”
Section: Introductionmentioning
confidence: 97%